Prenatal Brain MR Imaging: Reference Linear Biometric Centiles between 20 and 24 Gestational Weeks - Conte, G.; Milani, S.; Palumbo, G.; Talenti, G.; Boito, S.; Rustico, M.; Triulzi, F.; Righini, A.; Izzo, G.; Doneda, C.; Zolin, A.; Parazzini, C. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Evaluation of biometry is a fundamental step in prenatal brain MR imaging. While different studies have reported reference centiles for MR imaging biometric data of fetuses in the late second and third trimesters of gestation, no one has reported them in fetuses in the early second trimester. We report centiles of normal MR imaging linear biometric data of a large cohort of fetal brains within 24 weeks of gestation.MATERIALS AND METHODS: From the data bases of 2 referral centers of fetal medicine, accounting for 3850 examinations, we retrospectively collected 169 prenatal brain MR imaging examinations of singleton pregnancies, between 20 and 24 weeks of gestational age, with normal brain anatomy at MR imaging and normal postnatal neurologic development. To trace the reference centiles, we used the CG-LMS method.RESULTS: Reference biometric centiles for the developing structures of the cerebrum, cerebellum, brain stem, and theca were obtained. The overall interassessor agreement was adequate for all measurements.CONCLUSIONS: Reference biometric centiles of the brain structures in fetuses between 20 and 24 weeks of gestational age may be a reliable tool in assessing fetal brain development.BPDbiparietal diameterLLDlatero-lateral diameterCSAclivo-supraoccipital angleFODfronto-occipital diameterGAgestational ageLCClength of the corpus callosumAPDantero-posterior diameterCCDcranio-caudal diameter